Single-shot 3D imaging of hydroxyl radicals in the vicinity of a gliding arc discharge. (27th April 2021) - Bao, Yupan; Dorozynska, Karolina; Stamatoglou, Panagiota; Kong, Chengdong; Hurtig, Tomas; Pfaff, Sebastian; Zetterberg, Johan; Richter, Mattias; Kristensson, Elias; Ehn, Andreas
Abstract: Plasma-related studies in gas phase are challenging to carry out due to plasma's transient and unpredictable behavior, excessive luminosity emission, 3D complexity and aggressive chemistry and physiochemical interactions that are easily affected by external probing. Laser-induced fluorescence is a robust technique for non-intrusive investigations of plasma-produced species. In this letter, we present 3D distributions of ground state hydroxyl radicals (OH) radicals in the vicinity of a glow-type gliding arc plasma. Such radical distributions are captured instantaneously in one single camera acquisition by combining structured laser illumination and a lock-in based imaging analysis method called FRAME. The interference of plasma emission is automatically subtracted by the FRAME technique. In addition, the orientation of the plasma discharge can be reconstructed from the 3D data matrix, which can then be used to calculate 2D distributions of ground state OH radicals in a plane perpendicular to the orientation of the plasma channel. Our results indicate that OH distributions around a gliding arc are strongly affected by gas dynamics. We believe that the ability to instantaneously capture 3D transient molecular distributions in a plasma discharge, with minimal plasma emission interference, will have a strong impact on the plasma community for in situ investigations of plasma-induced chemistry and physics.